Characteristics and health effects of volatile organic compound emissions during paper and cardboard recycling. (May 2020) - Nabizadeh, Ramin; Sorooshian, Armin; Delikhoon, Mahdieh; Baghani, Abbas Norouzian; Golbaz, Somayeh; Aghaei, Mina; Barkhordari, Abdullah
Highlights: VOC emissions were studied for a waste paper and cardboard recycling factory. VOC concentrations reported for multiple factory sections. Total HQ for VOCs in recycling processes was more than the acceptable limit. LTCRs for VOCs in different sites of PCSWRF ranged from 1.21 × 10 −4 to 1.05 × 10 −5 . Exposure indices of VOCs for residents in PCSWRF exceeded the acceptable limit. Abstract: Urbanization generates increased amounts of solid wastes in cities and as a consequence leads to high air pollution levels. As a result of these trends, the subject of air quality management for sustainable concept of cities has received increasing attention. This work characterized volatile organic compound (VOC) emissions and health effects at different processing stages in a recycling facility for waste paper and cardboard. The highest total VOC levels were observed in the conveyor belt line one (5.23 ± 0.33 mg/m 3 ), followed by a baling machine (1.38 ± 0.07 mg/m 3 ), conveyor belt line two (1.34 ± 0.08 mg/m 3 ), tipping floor line one (1.22 ± 0.07 mg/m 3 ), and manual separation line one (1.20 ± 0.06 mg/m 3 ). Hence, exposure to VOCs lead to high health risks in this PCSWRF, especially at the manual separation stage (HQ = 2.7–3 and lifetime cancer risks (LTCRs) = 1.11 × 10 −4 - 1.03 × 10 −4 ), and strategies such as adjustment of the factory to enclose the conveyors, designing proper ventilation and air conditioning systems, minimization of VOC-contaminated waste generation (pre-treatment), and using personal protective equipment should be considered to eliminate pollutants and to protect workers from the non-carcinogenic and carcinogenic effects.